Non-selective area doping of rare-earth material with co-doping / Yap Yen - Yap, Yen (2009)
In this dissertation, erbium/aluminium (Er/Al) and erbium/ytterbium (Er/Yb) codoped on silica-on-silicon waveguide films were fabricated by flame hydrolysis deposition (FHD) via solution doping. Based on the morphology and microstructure observations, the layers pre-sintered around 800˚C provide the best surface adherence for solution doping. A few process parameters involved in solution doping has been investigated to study the impregnation of rare-earth in planar waveguide. It is observed that the solution strength and dipping period strongly influenced the RE concentration in silica film. Multiple solution doping method was demonstrated in the present work. The results indicated that the multiple cycles of solution doping of the soot layer increases the rare-earth concentration in the glass layer.